Pilot Innovative Territorial Clusters in Russia: A Sustainable Development Mode - Evgeniy Kutsenko (Foresight and STI Governance, 2015)
Leading countries consider regional clusters an efficient tool of interaction between actors of a regional innovation system, which enables new poles of economic growth to be formed. There is a large literature describing the positive experience of public support for clusters. In Russia, this process is still at an early stage. Russia’s strategy of innovative development up to 2020 includes a programme for supporting pilot innovative regional clusters.